Participation in a Resident-as-Teacher Rotation: Motivations of and Impacts on Faculty Coaches. (15th June 2022) - Marcus, Carolyn H.; Michelson, Catherine D.; Luff, Donna; Newman, Lori R.
Abstract : Purpose: Coaching in medical education is increasingly used for trainee development for a variety of skills, including improving trainee teaching skills through resident-as-teacher programs. Faculty who serve as coaches commit significant effort to the coaching role, often without protected time or support. Little is known about faculty motivations to participate in coaching programs or how the coaching experience affects the faculty. This study explored faculty coaches' motivations to participate as coaches in a resident-as-teacher rotation and the impacts they experienced as a result of their participation. Method: In this qualitative study, authors conducted 14 semistructured interviews in 2019 with faculty coaches from a single resident-as-teacher program in Boston, Massachusetts. Authors analyzed the transcripts using thematic analysis to develop a conceptual framework. Results: Faculty coaches' motivations for initial participation included a sense of honor; a sense of duty; perception of competence; interest in promoting medical education; and desire for increased connectedness. These motivations all related to a larger theme of educator identity. Coaches identified 3 main impacts from participation: improvement in their own teaching, personal satisfaction from helping others and seeing improvement in their learners, and increased connectedness. These impacts affirmed the coaches' educator identity and led to ongoing motivation to participate. They also contributed to the coaches' well-being at work. Conclusions: Faculty were initially motivated to participate as coaches in a resident-as-teacher rotation based on their identity as educators. The benefits achieved—improvement in own teaching, personal satisfaction, and increased connectedness—affirmed their educator identity and led to ongoing participation and increased well-being at work. These motivations and impacts are important to consider as future programs are developed and coaches are recruited for programs across undergraduate, graduate, and continuing medical education settings.